Restating Internal Control Reports Following Financial Statement Restatements: Determinants and Consequences* - Feng, Mei; Li, Chan; Raghunandan, K.; Sun, Lili (Contemporary Accounting Research, 2022)
ABSTRACT After restating their financial statements, companies may voluntarily restate their previously issued internal control (IC) reports for the financial statement (FS) misstatement periods, changing them from “effective” to “ineffective.” This paper examines the determinants and consequences of IC restatements, which have been of concern to financial statement users. When announcing these IC restatements, companies often provide a detailed explanation of the IC problems and a discussion of their plans to remediate these problems. We find that companies with less severe IC problems that can be remediated more quickly are more likely to restate their IC reports. Moreover, these results are driven by companies with a higher need for external financing, suggesting that IC restaters voluntarily restate their IC reports in order to inform investors about their less severe IC material weaknesses and their plans to improve IC quality. Finally, we find that, relative to other FS restatement companies, IC restaters have a lower likelihood of CFO turnover and auditor resignation following the FS restatement. Taken together, our results suggest that voluntary IC restatements are used by IC restaters as a means to separate themselves from other FS restatement companies with more severe control problems and slower remediation plans. Our findings also indicate that studies investigating IC quality and related disclosures need to distinguish between IC restaters and other FS restatement companies because of the different characteristics and consequences between the two groups.